Analisis Kesantunan Tindak Tutur Direktif Guru dalam Proses Pembelajaran di Sekolah Dasar - Wirma Lasri; Nurmalina Nurmalina; Putri Hana Pebriana (Universitas Negeri Makassar, 2021)
This study aims to describe the form of directive speech acts used by teachers in the learning process, describe directive speech acts used by teachers, and describe the context of the situation of teacher directive speech acts in the learning process at the 001 Pangkalan public elementary school. The research method used is descriptive qualitative research method, with the steps of the pre-field stage, the stage of field activities, data collection, and intensive analysis stage. The results showed that of the 12 elementary school teachers studied, all of them had good directive speech acts. The conclusion of this study is that the politeness of the teacher's directive speech acts in the learning process at the 001 base public elementary school is quite good and needs to be improved. Of all types of directive speech acts, the most dominant that emerges from the teacher's speech is the directive command speech act. Efforts are needed to improve continuous pedagogic competence in order to improve teacher skills in applying all directive speech acts so that teacher competence increases.